Performance comparison of PID tuning by using Ziegler-Nichols and particle swarm optimization approaches in a water control system - Edaris, Zahratul Laily; Abdul Rahman, Syariza (Universiti Utara Malaysia, 2016)
Tuning the gain of Proportional-Integral Derivative (PID) controller in a process control system is exceptionally paramount since correct tuning would help a control process response without steady state error and overshoot. As the conventional gain tuning of PID controller, the Ziegler-Nichols (ZN) approach generally delivers an enormous overshoot; therefore, current heuristics approach, namely Particle Swarm Optimization (PSO) is utilized.A tuning problem of a single tank water level dynamic control system is presented.The best PID controller parameters are determined by using the ZN and PSO approaches. Comparisons of process time performance and the performance measurement of the system are made in order to evaluate both approaches in terms of their step response through the MATLAB/Simulink platform.The results demonstrate that the PSO approach produces promising results with lower overshoot compared to the ZN approach.It is found that the PSO approach would be advantageous for the industries related to single tank water control system for a better PID gain tuning.